Estimasi Stok Karbon Hutan Mangrove Di Wilayah Pesisir Kabupaten Langkat Provinsi Sumatra Utara - Reisha Azzahra Putri Restanta (Center for Environmental Research, LPPM, Universitas Sebelas Maret, 2026)
Carbon emissions into the atmosphere are one of the factors contributing to climate change. This condition is exacerbated by the increasing number of damaged ecosystems, including mangrove ecosystems. Mangrove forests are one of the coastal ecosystems that play an important role in mitigating climate change through blue carbon storage. This study aims to estimate the carbon stock of mangrove forests in the coastal area of Langkat Regency in 2018 and 2023 using Sentinel-2A satellite imagery and to calculate the spatial and temporal changes that have occurred. The methods used include image processing to obtain the Normalized Difference Vegetation Index (NDVI) value, which is linked to biomass stocks using a second-order polynomial regression model. The results show that in 2018, the area of high-density mangroves reached 13,567.54 ha with a total carbon stock of around 148.92 million tons of C. In 2023, the area of mangrove vegetation with high NDVI decreased slightly to 13,176.93 ha with a carbon stock of 133.85 million tons of C. The southern region of Langkat Regency, such as Tanjung Pura and Secanggang Districts, had the highest carbon concentration. Conversely, a decrease in carbon stock values was found in several parts of the northern coast. This study confirms that the use of satellite imagery and NDVI is effective for estimating mangrove carbon stocks spatially and temporally.